Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/jcmm.13898
|View full text |Cite
|
Sign up to set email alerts
|

Plasma derived from human umbilical cord blood: Potential cell‐additive or cell‐substitute therapeutic for neurodegenerative diseases

Abstract: Limited efficacy of current therapeutic approaches for neurodegenerative disease has led to increased interest in alternative therapies. Cord blood plasma (CBP) derived from human umbilical cord blood (hUCB) may be a potential therapeutic. Benefits of CBP injection into rodent models of aging or ischaemic stroke have been demonstrated, though how benefits are elicited is still unclear. The present study evaluated various factors within the same samples of CBP and human adult blood plasma/sera (ABP/S). Also, au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 57 publications
1
26
0
1
Order By: Relevance
“…In vitro cultures of human dental cells, hUCB-derived mesenchymal stem cells (MSCs), hUCB-derived T-lymphocytes, and human endothelial colony forming cells display improved cell viability from supplementation with cord blood plasma (CBP) [3841]. CBP is composed of a distinctive cytokine profile with low concetrations of several pro-inflammatory cytokines, as well as high amounts of growth factors [29, 38, 42, 43]. The view that CBP may confer equally potent therapeutic effects as hUCB is bolstered by the observations that anti-inflammation and neuroprotection afforded by hUCB cell transplantation [32, 4447] is achieved by CBP infusion in experimental stroke model [43, 48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro cultures of human dental cells, hUCB-derived mesenchymal stem cells (MSCs), hUCB-derived T-lymphocytes, and human endothelial colony forming cells display improved cell viability from supplementation with cord blood plasma (CBP) [3841]. CBP is composed of a distinctive cytokine profile with low concetrations of several pro-inflammatory cytokines, as well as high amounts of growth factors [29, 38, 42, 43]. The view that CBP may confer equally potent therapeutic effects as hUCB is bolstered by the observations that anti-inflammation and neuroprotection afforded by hUCB cell transplantation [32, 4447] is achieved by CBP infusion in experimental stroke model [43, 48].…”
Section: Introductionmentioning
confidence: 99%
“…CBP is composed of a distinctive cytokine profile with low concetrations of several pro-inflammatory cytokines, as well as high amounts of growth factors [29, 38, 42, 43]. The view that CBP may confer equally potent therapeutic effects as hUCB is bolstered by the observations that anti-inflammation and neuroprotection afforded by hUCB cell transplantation [32, 4447] is achieved by CBP infusion in experimental stroke model [43, 48]. Our recent study shows that intravenous hUCB-derived plasma administration into the 1-methyl-4-phenyl-1,2,3,6-tetrahydro-pyridine (MPTP)-induced rat PD model ameliorates motor function and improves survival of dopaminergic neurons while reducing pro-inflammatory cytokines in the substantia nigra pars compacta (SNpc) [49].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the umbilical cord could be a good source of plasma for treating endometrial pathologies and other regenerative medicine applications, as demonstrated by other groups (Castellano et al, 2017;Ehrhart et al, 2018). PRP has also been tested in women with either thin endometrium (Chang et al, 2019;Eftekhar et al, 2018;Kim, Shin et al, 2019;Molina et al, 2018;Nazari et al, 2016;Tandulwadkar et al, 2017) or AS (Javaheri et al, 2020;Zadehmodarres et al, 2017).…”
Section: Platelet-rich Plasmamentioning
confidence: 52%
“…Therefore, UCB is used as a cellular source for replenishing young immune cells to treat senile diseases. [6][7][8][9][10] In this article, we describe immune aging and the application of cord blood for rejuvenating aging immune cells against neoplastic diseases.…”
mentioning
confidence: 99%